Metabolic Dysregulation Contributes to the Progression of Alzheimer’s Disease - Yan, Xu; Hu, Yue; Wang, Biyao; Wang, Sijian; Zhang, Xinwen (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD) is an incurable neurodegenerative disease. Numerous studies have demonstrated a critical role for dysregulated glucose metabolism in its pathogenesis. In this review, we summarize metabolic alterations in aging brain and AD-related metabolic deficits associated with glucose metabolism dysregulation, glycolysis dysfunction, tricarboxylic acid (TCA) cycle, oxidative phosphorylation (OXPHOS) deficits, and pentose phosphate pathway impairment. Additionally, we discuss recent treatment strategies targeting metabolic defects in AD, including their limitations, in an effort to encourage the development of novel therapeutic strategies.